(Ab)scent aromas: Mapping the smell texture of the COVID-19 pandemic. Issue 1 (March 2023) - Allen, Louisa
This paper maps the smell texture of the COVID-19 pandemic. Media and official accounts of the pandemic have been dominated by statistical rates of viral infection and death, as well as visual images of overburdened hospitals and deserted city streets. Mobilising smell as a medium for knowing the world differently, this paper documents pandemic smell markers such as 'hand sanitizer', 'disinfectant' and 'breath and body odour'. To do this, it employs 'smellwalk' and 'urban wandering' methodologies in Bayside, a coastal town in Aotearoa-New Zealand. It argues the pandemic produces a specific smell texture, conceptualised as a momentary re-arrangement of the normal smellscape. This re-arrangement is signalled by both the presence of pandemic smell markers, and absence of normal smells which create atmospheres of 'uncertainty', 'anxiety' and 'dis-ease'. In accordance with other emerging sensory scholarship about the pandemic, the paper considers whether this change in smellscape constitutes a 'sensory revolution.'